If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 5)(2x + -12) = 0 Reorder the terms: (5 + 3x)(2x + -12) = 0 Reorder the terms: (5 + 3x)(-12 + 2x) = 0 Multiply (5 + 3x) * (-12 + 2x) (5(-12 + 2x) + 3x * (-12 + 2x)) = 0 ((-12 * 5 + 2x * 5) + 3x * (-12 + 2x)) = 0 ((-60 + 10x) + 3x * (-12 + 2x)) = 0 (-60 + 10x + (-12 * 3x + 2x * 3x)) = 0 (-60 + 10x + (-36x + 6x2)) = 0 Combine like terms: 10x + -36x = -26x (-60 + -26x + 6x2) = 0 Solving -60 + -26x + 6x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-30 + -13x + 3x2) = 0 Factor a trinomial. 2((-5 + -3x)(6 + -1x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-5 + -3x)' equal to zero and attempt to solve: Simplifying -5 + -3x = 0 Solving -5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = 0 + 5 -3x = 0 + 5 Combine like terms: 0 + 5 = 5 -3x = 5 Divide each side by '-3'. x = -1.666666667 Simplifying x = -1.666666667Subproblem 2
Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6Solution
x = {-1.666666667, 6}
| 6(x+1)=90 | | (5x+3)(x+6)=0 | | 4(a-1)=84 | | (x-6)(x^2-3x+4)= | | (5x+3)(x-6)=0 | | Log(2x-4)=4 | | (3x-5)(x-6)=0 | | 8x=(13x+3) | | (X*40)+(x*1.5*10)=923 | | 8x=13x+3 | | x+x-6=47 | | 4(r=20)=1/5(20r=400) | | 5x-3(2-1x)=1-2x | | 4x^2-3x+7=11 | | 2(a+b)-10= | | x=2y+3w | | 2(AB)-10= | | x^3+6x^2-36=0 | | 2(A*B)=10 | | x^3+6x^2-36=30 | | (2x+2)(5x^2+3x-2)= | | 5+x=x*2.37500 | | 10x^2+-21=0 | | 2x*x^2=6 | | e^5x-9=12 | | 6+12(10-x)=84 | | j-63/2=2 | | 3+(x-2)-3x=3(4x-2) | | -46-(-34)=X/4 | | 7x-4(x-3)=2y | | 5r-6=69 | | x+x-12%=47 |